Health-Related Quality of Life in Children With Kaposiform Hemangioendothelioma - Dai, Shiyi; Yang, Kaiying; Qiu, Tong; Zhou, Jiangyuan; Zhang, Xuepeng; Chen, Siyuan; Li, Lizhi; Ji, Yi (Frontiers in Pediatrics, 2022)
Background and objective: Kaposiform hemangioendothelioma (KHE) is a rare, aggressive and borderline vascular tumor mainly occurring in infants and children. The aim of this study was to determine the health-related quality of life (HRQOL) in children with KHE. Measures: A total of 91 children with KHE participated in this cross-sectional study. The HRQOL was assessed by the age-specific Pediatric Quality of Life Inventory Version 4.0 (PedsQL™ 4.0) Infant Scales, Family Information Form (FIF), Family Impact Module (FIM) and Generic Core Scales (GCS). For comparison, demographically matched healthy children were recruited as a control group. The main outcome measure of HRQOL was analyzed in the two groups. We determined related factors that influenced the HRQOL in children with KHE and their parents by using a stepwise multiple regression analysis. Results: The study found that the scores of each item in the family impact module (FIM) were lower than 75, which suggesting that KHE can make the parents of patients in a state of poor quality of life. The scores of physiological and psychosocial domains in all age groups of patients with KHE were lower than those of normal children (P < 0.01). Activity dysfunction is the factor influencing the physiological function score of all-age patients. KMP is the factor influencing the psychosocial function score of all-age patients. Conclusions: The findings presented here suggest that patients with KHE have a poor HRQOL. KMP and activity dysfunction are risk factors for poor HRQOL in patients with KHE. However, lesion size, lesion location and education level of the mother and father were not related to the HRQOL.